The Parasitic Infection in the common moorhen Gallinula chloropus Linnaeus, 1758 (Rallidae) from Basrah Governorate, Southern Iraq. - Al–Mansury, Hanan (Iraqi Journal of Aquaculture, 2025)
In the present study, we studied parasitic infestations of waterhen or swamp chicken (Gallinula chloropus). The samples were gathered during the period from January to December 2024, in different sites at Hammar Marsh Basrah Province. The findings revealed that 72.1% of the birds were infected with one or more parasite species, including Raillietina sp. and Hymenolepis sp.); cestodes (tapeworms) and nematodes, including Capillaria sp., Ascaridia dissimilis, and Congylonema ingluricola. A seasonal pattern was shown for infection rates, with the highest prevalence during the cooler months. In particular, the infection rates in winter and spring were 42.85% and 32.15%, respectively. Mixed infections predominated (50% infection) with double infections occurring in 33.3%. Of the parasites detected, the nematode genus Capillaria was found to have the highest infection rate of 28.8%, followed by Raillietina spp. at 23.0%. These findings indicate the high parasitic load in the common moorhen. Basrah area population, especially in winter times. The results also highlight the high proportion of polyparasitism in the wetland birds, indicating potential ecological and abiotic factors that may be influencing the transmission dynamics of parasites in these birds.